Australian Muslims' Visibility: The Politics of Oppression and Recognition - Cheikh Husain, Sara (Religions, 2023)
Muslims living in the West have been facing an increasing level of public scrutiny as political instability and conflicts continue to fester in many regions in the world especially involving Muslim-majority societies. The intense public gaze is even more critical and problematic for those Muslim individuals whose religiosity is more visible in the public space. Within this context, Islamophobia discourses ensure that Muslims in the West continue to be hyper-visible and seen as problematic. The perceived hyper-visibility of Muslim individuals and organisations in public space is reflective of a widespread notion that Muslims overall exhibit an excess of visible religiosity which can be both an affront to national identity and potentially a threat to social cohesion. This paper examines the politics of Muslims’ visibility from the perspective of Muslim Community Organisations (MCOs) with a particular focus on examining MCOs’ strategies and actions vis-à-vis the negative hyper-visibility of Muslimness. This paper’s findings suggest that MCOs utilise Muslims’ hyper-visibility as a mechanism to extend their access to public sites of visibility, deploying strategic interventions to contextualise their position within visibility sites defined by notions of Australianness.